Diagnóstico de las necesidades de educación formal en el área de las Tecnologías de Información y Comunicación en Costa Rica, 2016-2019 - Porras Santamaría, Sindy; Ramírez Molina, Alberto; Fernández Castro, Verni (Universidad de Costa Rica, 2020)
Due to the constant improvements of the Information and Communication Technologies (ICT), a concern came up to figure out if the major graduates on ICT careers have the knowledge and skills required by the Costa Rican society. Therefore, an opportunity was suggested to test the current theory, the employers opinions and the academic offer in public universities which will provide and identify aspects where there might be room for improvement. In the article provided, a qualitative methodology was utilized by doing a documental revision from recent studies at a national level related to ICT and the study curriculum of public universities in Costa Rica: Instituto Tecnológico de Costa Rica (TEC), Universidad de Costa Rica (UCR), Universidad Nacional (UNA), Universidad Estatal a Distancia (UNED) y Universidad Técnica Nacional (UTN). Furthermore, twenty six stakeholders from information technology companies were involved with graduates in this area, which provided a list of needs and improvements in the formal education. Among the aspects found, soft skills, specializations like Big Data, Deep Learning or Internet of things and the high demand of unsatisfied professionals. At last, a highlight of the study contributions input in the current final profile process, in the elaboration of new academic options o in the creation of current continuing programs.